Research activities of the department of Librarianship and theory of reading of St. Petersburg State University of Culture and Arts: modern state-of-the-arts and perspectives - A. S. Pavlova (Библиосфера)
The resume of research activities of the department of Librarianship and theory of reading of St. Petersburg State University of Culture and Arts in 2005–2007 is analyzed. The staff of the department is described. The main trends of scientific work and methods of their realization in academic process and library practice are examined. Some perspective ways of scientific activities of the department are proposed